Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1097/pai.0b013e31802ced25
|View full text |Cite
|
Sign up to set email alerts
|

A New Rabbit Monoclonal Antibody (4B5) for the Immunohistochemical (IHC) Determination of the HER2 Status in Breast Cancer: Comparison With CB11, Fluorescence In Situ Hybridization (FISH), and Interlaboratory Reproducibility

Abstract: The 2 methodologies in current clinical use to assess HER2 status in breast cancer are: fluorescence in situ hybridization (FISH) (gene amplification) and immunohistochemistry (protein over-expression). A consistent finding has been that 3% to 15% of breast cancers over-express HER2 protein without evidence for gene amplification. Accurate determination of the HER2 status has implications for selecting patients most likely to respond to trastuzumab. We report here our preliminary experience with a new anti-HER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 41 publications
3
40
1
2
Order By: Relevance
“…One study mentions a perfect interlaboratory concordance on a very limited number of cases. 27 Future studies are needed to assess this issue.…”
Section: Discussionmentioning
confidence: 99%
“…One study mentions a perfect interlaboratory concordance on a very limited number of cases. 27 Future studies are needed to assess this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Using FISH as the reference standard, it has recently been shown that the anti-HER2 4B5 rabbit monoclonal antibody provides high sensitivity, specificity, and interlaboratory reproducibility for the detection of HER2 status in breast cancer. 35 In our study, 4B5 demonstrated excellent interlaboratory reproducibility for the detection of HER2 status for each performed comparison (K w ϭ 1.00). The level of agreement between the consensus 4B5 and individual site assessment was satisfactory for all sites (K w ϭ 1.00).…”
mentioning
confidence: 95%
“…[85] Clinical assays to assess the HER2 status include IHC, which detects protein overexpression, or FISH, which detects gene amplification. [85][86][87] Both assays have been clinically validated in the above mentioned prospective randomized clinical trials and have received FDA approval for predicting a clinical response and patient benefit from HER2-targeted treatment. Published data from these clinical trials suggest that only those patients whose breast cancer demonstrates protein over-expression and/or gene amplification by the above assays are likely to benefit from therapy with Trastuzumab.…”
Section: Her2 In Breast Cancersmentioning
confidence: 99%